2020
DOI: 10.3390/genes11111338
|View full text |Cite
|
Sign up to set email alerts
|

Plastome Characterization and Phylogenomics of East Asian Beeches with a Special Emphasis on Fagus multinervis on Ulleung Island, Korea

Abstract: Beech trees of the genus Fagus (Fagaceae) are monoecious and distributed in the Northern Hemisphere. They represent an important component of mixed broad-leaved evergreen–deciduous forests and are an economically important source of timber. Despite their ecological and economical importance, however, little is known regarding the overall plastome evolution among Fagus species in East Asia. In particular, the taxonomic position and status of F. multinervis, a beech species endemic to Ulleung Island of Korea, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…As expected, the plastomes of Hosta species representing three subgenera were highly conserved, with a total length ranging from 156,419 to 156,755 bp, and all contained 37.8–37.82% GC content and showed no structural variation or gene content rearrangements ( Table 1 ). The highly conserved nature of plastomes among congeneric species is consistent with that of other angiosperms in East Asia (e.g., [ 26 , 28 , 29 , 30 , 35 , 36 , 37 ]). Despite the conserved nature of the 11 Hosta plastomes generated in this study, they will be highly valuable and of great importance as references for additional Hosta species, especially those from Japan (subg.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As expected, the plastomes of Hosta species representing three subgenera were highly conserved, with a total length ranging from 156,419 to 156,755 bp, and all contained 37.8–37.82% GC content and showed no structural variation or gene content rearrangements ( Table 1 ). The highly conserved nature of plastomes among congeneric species is consistent with that of other angiosperms in East Asia (e.g., [ 26 , 28 , 29 , 30 , 35 , 36 , 37 ]). Despite the conserved nature of the 11 Hosta plastomes generated in this study, they will be highly valuable and of great importance as references for additional Hosta species, especially those from Japan (subg.…”
Section: Discussionsupporting
confidence: 74%
“…As complementary to nuclear genes to document reticulate evolution and introgression, plastome phylogenomic studies have provided valuable information for resolving phylogenetic relationships at various taxonomic levels. Recently, complete plastome sequences have proven useful in understanding the evolutionary history of closely related species in East Asia (e.g., [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]). Furthermore, rapid accumulation of complete plastome sequences in the family Asparagaceae (55 plastome sequences; GenBank accessed 20 July 2021) serves as a reference, allowing us to reconstruct a robust phylogenetic framework among major lineages within the family as well as to gain insight into plastome evolution (e.g., [ 32 ]).…”
Section: Introductionmentioning
confidence: 99%
“…After assembling, the sequences were manually checked, in case of presence of ambiguous nucleotides manual curation was done with the assistance of reads mapped to a genome with bwa-mem [ 33 ] and visualization of the results in Tablet software [ 34 ]. Coding sequences and RNA elements annotation was done with GeSeq ChloroBox [ 35 ] using chloroplast genomes of F. crenata ( NC_041252; [ 36 ]), F. engleriana (KX852398; [ 37 ]) F. japonica (MT762294; [ 38 ]) and F. sylvatica (NC_041437; [ 39 ]) as references. Postprocessed annotated genomes where uploaded to GenBank, for accession numbers see Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenetic analysis was done with on the basis of the dataset of the 18 Fagus sylvatica assemblies to which the complete chloroplast genomes of F. crenata ( NC_041252; [ 36 ]), F. japonica (MT762294; [ 38 ]) and F. engleriana (KX852398; [ 37 ]) before alignment as described above. Phylogenetic reconstructions were done using IQ-TREE with the GTR+I+R model [ 47 , 48 , 49 ] and 1000 bootstrap replicates.…”
Section: Methodsmentioning
confidence: 99%
“…The narrow endemic Pinus torreyana, for example, had five SNPs between the plastid genomes of two individuals from both parts of its disjunct distribution range (Whittall et al, 2010, indels not reported). Similarly, at least two SNPs and one indel were found between two plastid genomes of Fagus multinervis endemic to Ulleung Island off the South Korean coast (Yang et al, 2020). However, it is not possible to evaluate the genetic diversity of the species or any well-founded conservation genetic assessments based on the sequences of two plastid genomes alone.…”
Section: Phylogenetic Position Of C Bakuense Based On Complete Plastid Genomesmentioning
confidence: 99%